Investigation of Experimental Factors That Underlie BRCA1/2 mRNA Isoform Expression Variation: Recommendations for Utilizing Targeted RNA Sequencing to Evaluate Potential Spliceogenic Variants - Lattimore, Vanessa L.; Pearson, John F.; Currie, Margaret J.; Spurdle, Amanda B.; , kConFab Investigators; Robinson, Bridget A.; Walker, Logan C. (Frontiers in Oncology, 2018)
PCR-based RNA splicing assays are commonly used in diagnostic and research settings to assess the potential effects of variants of uncertain clinical significance in BRCA1 and BRCA2. The ENIGMA (Evidence-based Network for the Interpretation of Germline Mutant Alleles) consortium completed a multicentre investigation to evaluate differences in assay design and the integrity of published data, raising a number of methodological questions associated with cell culture conditions and PCR-based protocols. We utilised targeted RNA-seq to re-assess BRCA1 and BRCA2 mRNA isoform expression patterns in lymphoblastoid cell lines (LCLs) previously used in the multicentre ENIGMA study. Capture of the targeted cDNA sequences was carried out using 34 BRCA1 and 28 BRCA2 oligonucleotides from the Illumina Truseq Targeted RNA Expression platform. Our results show that targeted RNA-seq analysis of LCLs overcomes many of the methodology limitations associated with PCR-based assays leading us to make the following observations and recommendations: 1) Technical replicates (n>2) of variant carriers to capture methodology induced variability associated with RNA-seq assays, 2) LCLs can undergo multiple freeze/thaw cycles and can be cultured up to 2 weeks without noticeably influencing isoform expression levels, 3) Non-sense mediated decay inhibitors are essential prior to splicing assays for comprehensive mRNA isoform detection, 4) Quantitative assessment of exon:exon junction levels across BRCA1 and BRCA2 can help distinguish between normal and aberrant isoform expression patterns. Experimentally derived recommendations from this study will facilitate the application of targeted RNA-seq platforms for the accurate quantitative investigation of mRNA aberrations associated with sequence variants of uncertain clinical significance.